2018
DOI: 10.1016/j.jhydrol.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Declines in the dissolved organic carbon (DOC) concentration and flux from the UK

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 65 publications
0
35
2
Order By: Relevance
“…However, it does imply that at individual works, sharp changes can occur. Worrall et al () found that the median step change in DOC concentration, for those river records where a significant step decrease was observed, was 41% decline.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it does imply that at individual works, sharp changes can occur. Worrall et al () found that the median step change in DOC concentration, for those river records where a significant step decrease was observed, was 41% decline.…”
Section: Resultsmentioning
confidence: 99%
“…The least squares mean difference between sewage discharge and control reaches was 0.19 (±0.04), and this would mean that a sewage discharge increases the downstream DOC concentration of the receiving river water by 19%. Therefore, if the entire source of DOC from the sewage discharge were shut off, then the concentration observed in the river downstream of STWs would decrease by 16%, far lower than the average 41% observed for step changes at tidal limit sites as measured in Worrall et al ().…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations